2014
DOI: 10.1002/mrc.4123
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic NMR study of cyclic derivatives of pyridoxine

Abstract: A series of pyridoxine derivatives was investigated by (1) H and 2D nuclear overhauser enhancement spectroscopy (NOESY) NMR. The free energies of activation for the pyridyl-oxygen rotation of the 2,4-dinitrophenyl ether of the seven-membered acetals of pyridoxine were measured by dynamic NMR. A conformational exchange between the chair and twist forms of the seven-membered acetal ring was confirmed by dynamic NMR and STO3G computations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The results are presented in Table . Obtained energy barriers are in good agreement with literature data and the values of previously studied pyridoxine derivatives …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The results are presented in Table . Obtained energy barriers are in good agreement with literature data and the values of previously studied pyridoxine derivatives …”
Section: Resultssupporting
confidence: 87%
“…The comparison of obtained results with our previous studies reveals the significant influence of dynamics of the adjacent conformational processes on each other. It was found that an increase in the seven‐membered cycle transformation rate leads to the raise of activation energies for the 2,4‐dinitrophenyl group rotation (50–53 kJ/mol for acetal derivatives, 46 kJ/mol for compound III , and 41–44 kJ/mol for ketals). The rotation of 2‐nitrophenyl group around one single bond is less dependent on the changes of distant substituents, and its activation barriers remain almost the same for all studied compounds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations